2018
DOI: 10.1021/acsami.7b14443
|View full text |Cite
|
Sign up to set email alerts
|

Fe–N-Doped Mesoporous Carbon with Dual Active Sites Loaded on Reduced Graphene Oxides for Efficient Oxygen Reduction Catalysts

Abstract: Transition metal/nitrogen/carbon (M-N/C) catalysts are considered as one of the most promising candidates to replace Pt/C catalysts for oxygen reduction reactions (ORRs). Here, we have designed novel reduced graphene oxide (rGO)-supported Fe-N-doped carbon (Fe-N-C/rGO) catalysts via simple pyrolysis of polypyrrole (Ppy)-FeO-GO composites. The as-prepared catalysts induced an onset potential of 0.94 V and a half-wave potential of 0.81 V in alkaline solutions, which is much better than those of the counterpart N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 49 publications
4
53
0
Order By: Relevance
“…As presented in Figure 10A, compared with retained 85.68% for Pt/C, the value of current density for HCN-FNFCG-650 is still kept 92.83% of the initial value after 9000-second continuous tests. 4,47,55 While the small change of the HCN-FNFCG-650 has been found at the same conditions. The tolerances to methanol poisoning effect were investigated by chronoamperometric response tests with absolute methanol added; other test conditions are at the same as the stability tests.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…As presented in Figure 10A, compared with retained 85.68% for Pt/C, the value of current density for HCN-FNFCG-650 is still kept 92.83% of the initial value after 9000-second continuous tests. 4,47,55 While the small change of the HCN-FNFCG-650 has been found at the same conditions. The tolerances to methanol poisoning effect were investigated by chronoamperometric response tests with absolute methanol added; other test conditions are at the same as the stability tests.…”
Section: Resultssupporting
confidence: 55%
“…The result of methanol measurement for 20% Pt/C catalyst is also confirmed by previous related methanol tests. 4,47,55 While the small change of the HCN-FNFCG-650 has been found at the same conditions. These results indicated that the HCN-FNFCG-650 has a good immunity to methanol poisoning effect.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Generally, the doped N atoms can be separated into sp 2 hybridized graphitic N, pyridinic N, sp 3 hybridized pyrrolic N, and oxidized N species, among which the pyridinic N has been proved to play a vital role in the process of ORR 69,117. A three‐step carbonization process for synthesizing nitrogen‐doped porous carbon/carbon nanotubes from the MOF‐55 has been proposed, which presented excellent ORR activity in alkaline electrolyte with even more positive E onset and E 1/2 compared to the commercial Pt/C catalysts 118. The outstanding ORR performance is believed to be mainly due to the synergy of rich nitrogen doping, high graphitic degree, and large surface area.…”
Section: Orr Performance and Active Site Researchmentioning
confidence: 99%